Nature's perspective : an object-oriented ontological interpretation of nature in tourism, in times of global warming - Parada, Maria Enriqueta Saenz, 1968- (2017)
This theoretical work presents an object- oriented perspective to nature- based tourism in Iceland with the purpose of bringing about a more sustainable appreciation of nature and the Earth. It discusses tourism as a geophysical force in the Anthropocene, when total global emissions become a critical factor for the outlook of future climate stability. It also discusses the conception and practice of the tourism industry in Iceland, as well as the transformations that nature has undergone under the hand of the industry and society in general. The research also focuses on the concept of hyperobjects, as presented by Timothy Morton1, as well as on the challenges that tourism faces in an ecology where global warming is changing not only global weather patterns but also the geology of the Earth itself. Finally, the paper focuses on the role of speculative design as the venue to present a more ecological view of the Earth. The research concludes that to achieve this, speculative design could build on the notion of an ecology where the interactions of objects come to rule, eliminating so current social interpretations of a word, nature and environment. The paper concludes that in order to hear what the Earth is trying to tell us, we need to rethink the role of humans on Earth and shift our focus of concerns from the realm of humans to the objects in nature.